Potential of Theranostics in Visualisation of the Tumour Microenvironment and Elimination of Its Immunosuppressive Components - O. E. Molchanov; D. N. Maystrenko; A. A. Stanzhevskiy (Регуляторные исследования и экспертиза лекарственных средств, 2022)
Theranostics is a promising branch of nuclear medicine that uses radiopharmaceuticals for diagnosis and treatment of cancer, and immunotheranostics is a special area in it. The aim of the study was to summarise the potential of theranostics for visualisation of the tumour microenvironment and elimination of its immunosuppressive components. The article presents up-to-date information on the composition and interaction of various cell subpopulations in the tumour microenvironment, as well as on the role of cancer stem cells in its formation. It describes defects of signalling pathways and potential targets for theranostics of cancer stem cells. Also, the article provides a description of the mechanism of interaction between the tumour and the immune system in the process of carcinogenesis. The review offers a detailed analysis of approaches to assessing the type of tumour microenvironment in order to individualise treatment and develop a rational design of clinical studies of theranostic couples. The authors present their own data on the distribution of subpopulations of lymphocytes and myeloid-derived suppressor cells in patients with metastatic tumours. The authors have considered the nuances of creating and using various molecules for targeted delivery in the development of diagnostic and therapeutic radiopharmaceuticals. The most promising diagnostic and therapeutic isotopes are described from the point of view of assessing the microenvironment and the possibility of influencing it. The article highlights modern and promising methods of pre-targeting to reduce the toxicity and increase the effectiveness of theranostics. Furthermore, having compared the advantages and disadvantages of theranostics with those of other systemic treatment options for metastatic tumours, the authors outline possible ways to overcome the shortcomings of theranostics.